2019
DOI: 10.3390/antiox8090364
|View full text |Cite
|
Sign up to set email alerts
|

Capsaicinoids, Polyphenols and Antioxidant Activities of Capsicum annuum: Comparative Study of the Effect of Ripening Stage and Cooking Methods

Abstract: Peppers (Capsicum annuum L.) are an important crop usually consumed as food or spices. Peppers contain a wide range of phytochemicals, such as capsaicinoids, phenolics, ascorbic acid, and carotenoids. Capsaicinoids impart the characteristic pungent taste. The study analyzed capsaicinoids and other bioactive compounds in different pepper cultivars at both the mature green and red stages. The effect of roasting on their nutritional content was also investigated. In the cultivars tested, the levels of capsaicin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
71
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(97 citation statements)
references
References 46 publications
10
71
0
4
Order By: Relevance
“…From a redox viewpoint, it has been found that reactive oxygen species (ROS) metabolism is also affected during fruit ripening, leading to major changes in total soluble reducing equivalents and the antioxidant capacity in fruits [41]. The profile of the major non-enzymatic antioxidants, including ascorbate, glutathione, carotenoids and polyphenols, has been followed during ripening in pepper fruits [4,11,12,[42][43][44][45][46], but less is known on how enzymatic antioxidants evolve with this physiological process. These enzyme systems basically include superoxide dismutase (SOD), catalase (CAT) and the ascorbate-glutathione cycle as the primary defense barriers against ROS, and some NADP-dehydrogenases as a secondary system to help the antioxidative enzymatic block.…”
Section: Introductionmentioning
confidence: 99%
“…From a redox viewpoint, it has been found that reactive oxygen species (ROS) metabolism is also affected during fruit ripening, leading to major changes in total soluble reducing equivalents and the antioxidant capacity in fruits [41]. The profile of the major non-enzymatic antioxidants, including ascorbate, glutathione, carotenoids and polyphenols, has been followed during ripening in pepper fruits [4,11,12,[42][43][44][45][46], but less is known on how enzymatic antioxidants evolve with this physiological process. These enzyme systems basically include superoxide dismutase (SOD), catalase (CAT) and the ascorbate-glutathione cycle as the primary defense barriers against ROS, and some NADP-dehydrogenases as a secondary system to help the antioxidative enzymatic block.…”
Section: Introductionmentioning
confidence: 99%
“…Hamed, Kalita, Bartolo, and Jayanty (2019) reported that the variations in the accumulation of capsaicinoids can be attributed to intrinsic genetic factors of each genotype and to environmental conditions; also, levels of capsaicinoid compounds, especially capsaicin, could change with the maturation stage, or even with water stress during plant cultivation as found before by Mahendran and Bandara (2000). Other group of researchers (Gurung, Techawongstien, Suriharn, & Techawongstien, 2011) worked with 14 chili cultivars with different genotype, pungency, and environment, and concluded that genotype had a major role in the accumulation and content of capsaicinoids.…”
Section: Biochemical Compositionmentioning
confidence: 71%
“…Additionally, consumers appreciate the valuable health properties that are attributed to this food group. In fact, peppers are known to have also been used as medicinal plants because of their substantial contents of bioactive compounds, which provide health benefits to consumers [ 7 , 8 ]. Capsaicinoids and capsinoids, which are among those bioactive compounds of interest, are also responsible for the pungency of chili peppers, which is one of their most important commercial traits [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, and depending on the attributes that are sought by producers (color, pungency, etc. ), the fruit optimal harvesting moment will vary [ 7 , 27 ].…”
Section: Introductionmentioning
confidence: 99%